2021
DOI: 10.3389/fphys.2021.732084
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Yes-Associated Protein/PDZ-Binding Motif Pathway Contributes to Endothelial Dysfunction and Vascular Inflammation in AngiotensinII Hypertension

Abstract: Yes-associated protein (YAP) and its associated coactivator of PDZ-binding motif (TAZ) are co-transcriptional regulators and down effectors of the Hippo signaling pathway. Recent studies have shown that the Hippo/YAP signaling pathway may play a role in mediating vascular homeostasis. This study investigated the role of YAP/TAZ in endothelial dysfunction and vascular inflammation in angiotensin (Ang)II hypertensive mice. The infusion of AngII (1.1 mg/kg/day by mini-pump) for 3 weeks induced the activation of Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Atherosclerosis is the main inducer of cardiovascular diseases. Studies have confirmed that the activation of YAP/TAZ in endothelial cells plays an important role in the occurrence and development of atherosclerosis by promoting an inflammatory response (12,67,73,74). Overexpression of YAP in an ApoE −/− mouse model upregulated the inflammatory related factors in arterial endothelial cells, such as IL-6, VCAM-1 and IL-8, and thus increased the atherosclerotic plaque and lesion range in aortic arch (8,33).…”
Section: Effect Of Yes-associated Protein/transcriptional Co-activato...mentioning
confidence: 88%
See 1 more Smart Citation
“…Atherosclerosis is the main inducer of cardiovascular diseases. Studies have confirmed that the activation of YAP/TAZ in endothelial cells plays an important role in the occurrence and development of atherosclerosis by promoting an inflammatory response (12,67,73,74). Overexpression of YAP in an ApoE −/− mouse model upregulated the inflammatory related factors in arterial endothelial cells, such as IL-6, VCAM-1 and IL-8, and thus increased the atherosclerotic plaque and lesion range in aortic arch (8,33).…”
Section: Effect Of Yes-associated Protein/transcriptional Co-activato...mentioning
confidence: 88%
“…However, how the abovementioned factors regulate YAP/TAZ and whether there are other downstream target genes modulated by YAP/TAZ are not well clarified. Accumulating evidence has indicated that YAP/TAZ play a central role in modulating biological functions of the vascular endothelium, including inflammation, oxidative stress, and angiogenesis (12,67,(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87). Whether there are other biological functions of the vascular endothelium affected by YAP/TAZ are also worthy to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The knocking down of the YAP/TAZ can also significantly reduce the expression of VCAM1 induced by TNF-α [ 53 ], which suggests that the endothelial YAP/TAZ may assist a vascular repair by regulating the inflammatory reaction. The dephosphorylation/activation of the endothelial YAP/TAZ signal in a high glucose microenvironment is considered as the key link [ 54 ]; this will increase the endothelial inflammation and monocyte attachment [ 53 , 55 ].…”
Section: Yap/taz In Myocardial Infarction (Mi) and Cardiac Repair Aft...mentioning
confidence: 99%
“…Moreover, YAP aggravates the inflammatory response in the vascular endothelium under high glucose conditions. Similarly, in the aortas of Angiotensin II -induced hypertensive mice, treatment with the YAP/TAZ inhibitor v e r t e p o r fi n r e d u c e s m a c r o p h a g e i n fi l t r a t i o n a n d proinflammatory cytokine production (164). However, another study demonstrated that Tie2-mediated endothelial-specific knockout of Yap in mice resulted in mild endothelial inflammation and impaired microvessel permeability in lung, as evidenced by increased numbers of total cells, neutrophils, and macrophages and an increased neutrophil/macrophage ratio after LPS administration.…”
Section: Vascular Endothelial Cellsmentioning
confidence: 99%